2017
DOI: 10.1016/j.polymertesting.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Failure analysis of plain woven glass/epoxy laminates: Comparison of off-axis and biaxial tension loadings

Abstract: An experimental study was focused on investigation of the failure properties of plain woven glass/epoxy composites under offaxis and biaxial tension loading conditions. Four fibre orientations (0 ,15 ,30 and 45 with respect to the load direction) were considered for off-axis tests and two biaxial load ratios for biaxial tests to study failure characteristics and mechanism. Four classical polynomial failure criteria-Tsai-Hill, Hoffman, Tsai-Wu and Yeh-Stratton-were analysed comparatively to predict offaxis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 36 publications
1
15
0
3
Order By: Relevance
“…It suggested that this phenomenon may be a result of the interaction of the tensile and shear stresses. A similar mechanical response was also found by Cai et al [13,21] and Koohbor et al [4,15]. Godara et al [17] employed the digital image correlation technique (DIC) method to experimentally investigate the effects of the fiber orientation on the mesoscale deformation and the multiple failure mechanisms of the woven textile composite.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…It suggested that this phenomenon may be a result of the interaction of the tensile and shear stresses. A similar mechanical response was also found by Cai et al [13,21] and Koohbor et al [4,15]. Godara et al [17] employed the digital image correlation technique (DIC) method to experimentally investigate the effects of the fiber orientation on the mesoscale deformation and the multiple failure mechanisms of the woven textile composite.…”
Section: Introductionsupporting
confidence: 61%
“…Failure is expected to occur in the brushy fracture region, which supports the description earlier. Compared with the fractured sections of the fibers of on-axis specimens, there are numerous sites of oblique fracture sections of the fibers for off-axis specimens [13] (Fig. 10 d), in some extent indicating the characteristics of off-axis failure mechanism at micro-scale.…”
Section: Failure Mechanismmentioning
confidence: 96%
See 2 more Smart Citations
“…Existing studies provide different perspectives for understanding the influence of the fabric architecture and loading direction on the mechanical properties, and the damage behaviors of woven fabric composites [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Cai et al [ 6 , 7 ] investigated the tensile properties of unidirectional and woven fabric glass/epoxy composites under on- and off-axis loading and found that the Tsai-Wu failure criterion is more accurate with a modified interaction coefficient under multiaxial stress conditions compared with the Tsai-Hill, Hoffman and Yeh-Stratton criteria. Zhou et al [ 8 ] studied the damage evolutions of woven fabric composites with three different fabric architectures by monotonic and cyclic on- and off-axis tension tests.…”
Section: Introductionmentioning
confidence: 99%